Impact of affective picture and music stimuli on autonomic responses: characterisation of pauses between emotion blocks. (2018) - Goshvarpour, Atefeh; Abbasi, Ataollah; Goshvarpour, Ateke
The main goal of this study was to investigate the role of stimulus contents on physiological responses. Usually some pauses between the incentives are considered in an experiment to bring the physiological signals to the base. However, the role of these halts on emotional responses has not been carefully evaluated so far. Therefore, in the current study the effect of pauses between emotional blocks of an inducement was inspected. To this effect, autonomic signals were recorded using two emotion elicitation paradigms: image induction and music excerpts. Several standard and nonlinear features were extracted. The Mann-Whitney U-test was employed to determine the significant differences between the pause segments and rest condition. The results of this study indicated that pause duration between affective blocks of stimuli has a great impact on the emotional autonomic responses. The importance of specialised protocol designing for a specific biomedical signal is concluded from the findings.